Intifada Diplomatik: Negara-Negara Yang Menentang Israel dan Dampaknya Terhadap Lanskap Politik Global - Mohammad Ilham Fahmi Rusdi; Ulya, Nurul Fikriyatul; Halifah, Nur (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
This article discusses the phenomenon of the